Gestión municipal y calidad de servicio en la Municipalidad de Punchana 2024 - Del Prado Sanchez, Paul (2025)
The objective of this research work was to determine how municipal management is related to the quality of public service in the District Municipality of Punchana, 2024. The study is of a basic, quantitative, correlational type, adopting a non-experimental and transversal design. In this study, a non-probabilistic sampling was used, specifically for convenience. The population consisted of 30 workers. In this study, the survey and the questionnaire were used as instruments. In the results it could be observed that, out of a total of 30 respondents in municipal management and quality of service in the municipality of Punchana 2024, 3.3% responded that they neither agreed nor disagreed with the municipal management in the District Municipality of Punchana 2024, therefore, 6.7% commented that they disagreed, in addition 10.0% stated that they agreed, on the other hand, 33.3% expressed that they totally disagreed, while 46.7% stated that they totally agree with the municipal management in the District Municipality of Punchana 2024, with a significance value (observed critical value) 0.000<0.05 the null hypothesis was rejected and the alternative hypothesis was accepted, that is; Municipal management is significantly related to the quality of public service in the District Municipality of Punchana, 2024. Concluding that municipal management is significantly related to the quality of public service in the District Municipality of Punchana, 2024, Transparent and responsible management contributes to improving the quality of public services. When citizens perceive that resources are managed appropriately and that their needs are met, trust in municipal services increases, which raises their perception of quality.